Luxembourg : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper provides an overview of the impact of monetary policy on Luxembourg's macroeconomy. It analyzes the impact on the banking system, including risks that could result from normalization. It also studies the impact of accommodative monetary policy on the investment fund industry. Accommodative monetary policy has contributed to the performance of the Luxembourg economy through some expansion of aggregate demand and through its impact on the financial system. Banks have remained profitable and interest margins stable, while fee and commission income from the fund and other activity has been healthy. The investment fund industry has benefited from various factors such as portfolio rebalancing, search for yield, and other market developments leading to strong inflows into various classes of investment funds, and through strong valuation effects. Scenario analysis suggests that the fund industry could be adversely impacted by sharp interest rate increases and that, because of interconnections, the banking system would also be affected.